IMPLEMENTATION OF PRODUCT STANDARDIZATION POLICY SMALL AND MEDIUM INDUSTRY (IKM) IN WOOD PROCESSING RESULTS - Wijaya Wijaya; Sri Mulyani; Emiliana Emiliana (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2017)
The policy of the Minister of Trade which stipulates Ministerial Regulation No. 97 / M-DAG / PER / 12/2014 on the provisions on the export of forestry industry products implements the obligation to apply product standardization with SVLK (Timber Legality Verification System) to processed wood products from January 1, 2015. SVLK requirements for Small and Medium Enterprises (IKM), especially wood furniture and handicraft industries, are simplified in the form of self declaration as set forth in the document